Vochysia condorensis (Vochysiaceae), a new species from the Cordillera del Cóndor, Ecuador - Huamantupa-Chuquimaco, Isau; Neill, David A. (Phytotaxa, 2018)
Vochysia condorensis is described and illustrated as a new species from the Cordillera del Cóndor region of southeastern Ecuador, where it occurs exclusively on plateaus of quartzitic sandstone of the Hollín Formation and adjacent slopes. The species is placed in Vochysia section Ciliantha subsection Megalanthae and is compared with its most closely related congeners within the subsection: V. duquei and V. gigantea.